NSP4 antibody levels in rotavirus gastroenteritis patients with seizures. (March 2017) - Yeom, Jung Sook; Kim, Young-Soo; Jun, Jin-Su; Do, Hyun Jung; Park, Ji Sook; Seo, Ji-Hyun; Park, Eun Sil; Lim, Jae-Young; Woo, Hyang-Ok; Park, Chan-Hoo; Youn, Hee-Shang
Abstract: Background: Rotavirus nonstructural protein 4 (NSP4) has been suggested as a pathogen of rotavirus-associated seizures. We investigated pre-existing serum antibodies against NSP4 and VP6 (the most highly immunogenic rotavirus protein) in patients with rotavirus gastroenteritis and its correlation with the occurrence of seizures. Methods: With an enzyme-linked immunosorbent assay, IgG and IgA titers against NSP4 (genotype [A] and [B]) and VP6 were measured in acute-phase sera of 202 children aged 0.5–6.0 years with rotavirus gastroenteritis. The clinical characteristics and antibody levels were compared between patients with (seizure group) and without seizures (non-seizure group). Results: The non-seizure and seizure groups comprised 173 and 29 patients, respectively. Age, sex, hospital stay, presence of fever, white blood cell counts, C-reactive protein, vaccine status, IgG/IgA titers for VP6, and IgA titers for both NSP4s did not differ between the groups. The seizure group showed a lower level of IgG against NSP4 [A] (184.5 vs. 163.0 U/mL; P  = 0.03) and NSP4 [B] (269.0 vs. 196.0 U/mL; P  = 0.02). Delayed sampling time from the onset of gastroenteritis symptoms (3 vs. 2 days; P  = 0.02) and lower serum sodium level (133.4 vs. 136.3 mEq/L; P  < 0.01) were observed in the seizure group. Even after adjusting these factors, anti-NSP4 [A] IgG (OR 2.56 per 100 U/mL increment; 95% CI, 1.20–5.26, P  = 0.01) and anti-NSP4 [B] IgG (OR 1.51 per 100 U/mL-increment; 95% CI, 1.04–2.22, P  = 0.03) were independently associated with protection against seizures. Conclusions: Serum anti-NSP4 IgG might protect rotavirus-associated seizures. Highlights: The seizure group showed significantly lower serum level of IgG against NSP4s. IgG/IgA titers for VP6, and IgA titers for NSP4s did not differ between the groups. IgG against NSP4s were independently associated with seizure protection. Our data suggested serum anti-NSP4 IgG plays a possible role in seizure protection. Systemically circulating NSP4 might be associated with rotavirus-associated seizures.